Skeletal Muscle Mitochondrial Respiration Is Elevated in Female Cynomolgus Macaques Fed a Western Compared with a Mediterranean Diet - Gonzalez-Armenta, Jenny L (J Nutr, 2019)
BACKGROUND: Western diets are associated with increased incidences of obesity, hypertension, diabetes, and hypercholesterolemia, whereas Mediterranean diets, richer in polyphenols, monounsaturated fats, fruits, vegetables, poultry, and fish, appear to have cardiometabolic health benefits. Previous work has included population-based studies with limited evidence for causation or animal studies focused on single macro- or micronutrients; therefore, primate animal models provide an opportunity to determine potential mechanisms underlying the effects of dietary patterns on health and disease. OBJECTIVE: The aim of this study was to determine the effects of whole dietary patterns, either a Western or Mediterranean diet, on skeletal muscle mitochondrial bioenergetics in cynomolgus macaques. METHODS: In this study, 22 adult female cynomolgus macaques (∼11–14 y by dentition) were fed either a Western or Mediterranean diet for 30 mo. The Western diet was designed to mimic the diet of a middle-aged American woman and the Mediterranean diet included key aspects of Mediterranean diets studied in humans, such as plant-based proteins and fat, complex carbohydrates, and fiber. Diets were matched on macronutrient composition (16% protein, 54% carbohydrate, and 31% fat) and cholesterol content. Skeletal muscle was collected for high-resolution respirometry, citrate synthase activity, and western blot measurements. Pearson correlation analysis between respirometry measures and measures of carbohydrate metabolism was also performed. RESULTS: We found that consumption of a Western diet resulted in significantly higher mitochondrial respiration with fatty acid oxidation (FAO) (53%), FAO + complex I (52%), complex I + II (31%), max electron transport system (ETS) (31%), and ETS rotenone sensitive (31%) than did consumption of a Mediterranean diet. In addition, measures of respiration in response to fatty acids were significantly and positively correlated with both insulin resistance and plasma insulin concentrations. CONCLUSIONS: This study highlights the importance of dietary composition in mitochondrial bioenergetics and that diet can influence skeletal muscle mitochondrial respiration independently of other factors such as macronutrient composition.